A multi-stimuli-responsive tetraphenylethene derivative with high fluorescent emission in solid state. (January 2022) - Wang, Ling; Zhang, Rui; Huang, Ze; Guo, Shengmei; Yang, Jia-xiang; Kong, Lin
Abstract: In this study, a tetraphenylethene derivative 2-(4-(4-(4, 4, 5, 5-tetramethyl-1, 3, 2- dioxaborolan-2-yl)benzyloxy)phenyl)-3-(4-(1, 2, 2-triphenylvinyl)phenyl)acrylonitrile (abbreviated as TPEB ) modified with borate ester group had been designed and synthesized, which exhibited high quantum yield in solid state (Φ = 0.66) and multi-stimuli-responsive performance. For the first one, TPEB showed aggregation induced emission (AIE) feature, the fluorescence intensity of which in water/THF mixture ( f w  = 90%) was 131.4 times that in pure THF. Secondly, TPEB can respond to viscosity and the fluorescence intensity increased by 43.8 times in high-viscosity solvent (1400 cP) from that in 2 cP. Thirdly, TPEB exhibited reversible mechanofluorochromic (MFC) character between blue (482 nm) and yellow-green- coloured (505 nm) fluorescence during grinding-fuming process. Moreover, TPEB can recognize hypochlorite (ClO − ) under both UV–vis absorption and fluorescence emission modes with high selectivity. In the presence of ClO −, the UV–vis absorption band of TPEB red-shifted from 375 nm to 414 nm, which shifted from 501 m to 566 nm for fluorescence emission with 1.24 fold increase in intensity. The mechanism of multi-stimuli responsive performance was thoroughly studied through single crystal structure, scanning electron microscopy (SEM), powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC) and hybrid density functional theory (HDFT) calculation. Highlights: A multi-stimuli-responsive TPE derivative (TPEB ) had been synthesized. TPEB exhibited AIE/MFC feature and can respond to viscosity. TPEB recognized ClO - with high selectivity in both UV-vis and fluorescence modes. MFC application of TPEB as smart erasable ink. The mechanism of multi-stimuli-responsive performance was thoroughly studied.